2009
DOI: 10.1021/bi9000563
|View full text |Cite
|
Sign up to set email alerts
|

Activation of HydAΔEFG Requires a Preformed [4Fe-4S] Cluster

Abstract: The H-cluster is a complex bridged metal assembly at the active site of [FeFe]-hydrogenases that consists of a [4Fe-4S] subcluster bridged to a 2Fe-containing subcluster with unique nonprotein ligands, including carbon monoxide, cyanide, and a dithiolate ligand of unknown composition. Specific biosynthetic gene products (HydE, HydF, and HydG) responsible for the biosynthesis of the H-cluster and the maturation of active [FeFe]-hydrogenase have previously been identified and shown to be required for the heterol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

8
120
0
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(132 citation statements)
references
References 46 publications
8
120
0
4
Order By: Relevance
“…Detailed spectroscopic and structural studies of HydA ΔEFG have shown that it contains a [4Fe-4S] cluster and is poised to accept a 2Fe subcluster prior to activation by the accessory proteins (9,10). We have also shown that HydF purified from E. coli in which all three accessory proteins were coexpressed (HydF EG ) was competent in HydA ΔEFG activation, indicating that HydF acts as a scaffold or carrier protein during activation of HydA (20).…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…Detailed spectroscopic and structural studies of HydA ΔEFG have shown that it contains a [4Fe-4S] cluster and is poised to accept a 2Fe subcluster prior to activation by the accessory proteins (9,10). We have also shown that HydF purified from E. coli in which all three accessory proteins were coexpressed (HydF EG ) was competent in HydA ΔEFG activation, indicating that HydF acts as a scaffold or carrier protein during activation of HydA (20).…”
mentioning
confidence: 77%
“…Assembly of a catalytically competent H cluster requires the actions of three hydrogenase-specific accessory proteins, two of which (HydE and HydG) are radical S-adenosylmethionine (SAM) enzymes and the third of which (HydF) is a GTPase (7,8). These accessory proteins are directed at synthesis of the 2Fe subcluster of the H cluster, which is subsequently transferred to the hydrogenase structural protein (HydA) containing a preformed [4Fe-4S] cluster (9,10) to produce the active hydrogenase. The detailed stepwise mechanism of H-cluster assembly, as well as the specific roles of and interactions between the three accessory proteins in this assembly process, remains largely unknown.…”
mentioning
confidence: 99%
“…According to several recent in vitro studies, this process occurs in a multistep pathway, in which the [4Fe-4S] unit is synthesized by the Isc/Suf FeS general cell machinery, whereas the biosynthesis and insertion of the 2Fe subcluster, together with its ligands, is driven by HydE, HydG, and HydF maturases (5)(6)(7)(8)17). Current data indicate that the addition of the CO/CN Ϫ / dithiolate ligands to the 2Fe subcluster is accomplished through the action of the HydE/HydG radical SAM chemistry coupled to the presence of HydF, which would have a double involvement as scaffold and carrier to build and insert the modified 2Fe subcluster into a hydrogenase containing a preformed [4Fe-4S] unit (17)(18)(19)(20)(21).…”
mentioning
confidence: 99%
“…Already prior to the formation of [2Fe] pdt ‐HydA1, the [4Fe4S] cluster present in apo‐HydA1 is potentially detectable under our experimental conditions 8, 27. As seen in Figure 2 (spectrum a), the EPR spectrum of apo‐HydA1‐expressing cells featured a number of signals, but we could only observe minor differences compared to control samples of BL21(DE3) cells lacking the HydA1 plasmid (Supporting Information, Figure S2).…”
mentioning
confidence: 78%
“…Consequently, we assign the signal to the formation of [2Fe] pdt ‐HydA1, residing in the paramagnetic H ox ‐like state previously described as [4Fe‐4S] 2+ ‐[Fe I Fe II ] pdt 14, 16. To further support the assignment of the observed EPR signal we generated purified [2Fe] pdt ‐HydA1 ([2Fe] pdt ‐HydA1 pur ) through a modified literature protocol 8, 13, 27. The purified semi‐synthetic protein was oxidized by thionine to generate the H ox ‐like state, and the EPR spectrum of [2Fe] pdt ‐HydA1 pur showed the expected rhombic signal (Figure 2, spectrum d) 14.…”
mentioning
confidence: 80%